Sombreamento no desenvolvimeto de brotos de Ilex paraguariensis A.St.-Hil - Vuaden, Elisabete (2009)
This study aimed at evaluating the influence of the shade of both the crown and the ground in the development of sprouts of a plantation of Ilex paraguariensis after pruning. The experiment was carried out at the Experimental Area of the Federal University of Santa Maria. An experiment with 4 treatments in a randomized block design with 12 repetitions with 1 plant in each repetition was established. The yerba mate plants were pruned at 0,60 m high and the following treatments were used: T1 = Without crown shade, without soil coverage, T2 = Without crown shade, with soil coverage, T3 = With crown shade, without soil coverage, T4 = With crown shade, with soil coverage. The material used as organic coverage on the soil was the burlap from an eucalyptus plantation and the material from the pruning of Ilex paraguariensis. The crown shade of the trees was gotten by the use of a 50% shade screen, where the plants of Ilex Paraguariensis were shaded after midday. In September 2007, the trees were measured dendrometrically, their biomass was fractioned and, after that, these trees were submitted to their own treatments. In September 2008, plants of Ilex Paraguariensis were evaluated again. In order to determine the commercial biomass, 16 plants of yerba mate were collected; to the others, the commercial biomass was estimated by the sum of the biomass of the sprouts. It was verified that the green weight of the commercial biomass (bc) of plants of Ilex paraguariensis which had never been pruned had bigger correlation with the basal area at 0,6 m high (g0,6) and, in second place, with the total height (ht); the model that best described the commercial biomass of plants which had never been pruned was: ln bc = 9,6533 + 0,4412 ln (g0,6.ht); the commercial biomass of the sprouts can be estimated as function of the leafed length of the sprouts, with specific models for short sprouts, simple medium sprouts and composed medium sprouts; the partial shade of the yerba mate and the addition of dead coverage (T4) overcame the other treatments for all the variables; the addition of dead coverage (T2) generated bigger average than the crown shade itself (T3), for the variables sum of the leafed length, sum of the total length and commercial biomass; the pruned yerba mate plants' commercial biomass presented bigger correlation sum of leafed length, sum of total length and sum of number of leaves; the variable of easy measurement that best estimated the pruned yerba mate plants' commercial biomass was the medium length of the three longer branches (c3), resulting in the following equation: ln bc = 1,4722. ln c3; the correlation of the yerba mate plants' commercial biomass in the year 2007 with the commercial biomass in the year 2008 was 65%. The covariance analysis indicated that there was effect of the treatments only for error probability close to 10%.